Un tradicional ejemplo de confusión genealógica: a propósito de la muerte de Abd Al-Rahman "Sanchuelo" y Sancho Ibn Gómez (1009) - Torre Sevilla-Quiñones de León, Margarita (Estudios humanísticos. Geografía, historia y arte, 1997)
The most of historicians, who are dedicated on Spanish Early Middle Age, considers that the earl who died with Almanzor'son was García Gómez, count of Saldaña-Carrión. We have discovered, following arab chronicles, that this knight was, instead of García Gómez, his brother Sancho Gómez.